Post-activation potentiation: effect of recovery duration and gender on countermovement jump, agility, and linear speed in team-sport athletes - Asmadi Ishak (Tanjung Malim, 2023)
Post-activation potentiation: effect of recovery duration and gender on countermovement jump, agility, and linear speed in team-sport athletes by Asmadi Ishak